Branded content and luxury fashion brands: a study on the composition of fashion films - Atarama Rojas, Tomás (2022)
In the last decade, the use of fashion films as a strategic content in the fashion industry has acquired special relevance. The objectives of this research are aimed at framing fashion films within the framework of branded content and distinguishing their specific characteristics in the sector of luxury fashion brands, such as Louis Vuitton, Hermès, Burberry and Dior. To do this, a qualitative methodology is used to study the most representative fashion films of the selected brands through an aesthetic analysis and a diegetic analysis. The results of the research show that brands conceive fashion films as content marketing, advertainment and branded entertainment, with different aesthetic and narrative characteristics.